IN VITRO CHOLESTEROL BIOSYNTHESIS IN TESTICULAR TISSUE OF RAMS FED ON FLUORIDE SUPPLEMENTED RATION. - Λ. Abdul-Razzaq H.; A. Alnoor, S.; M. Hussain, S.; W.R. Mehdi , A. (The Iraqi Journal of Veterinary Medicine, 1994)
A study was carried out to investigate the effect of fluoride on cholesterol synthesis in testicular tissue of rams. Sodium fluoride was added to the rations at two levels (50 and 100 ppm) on dry weight basis. At the end of the experiment, the animals were sacrificed and the right testes of each animal was removed and incubated with 1-C1- acetate in the presence and absence of HCG. Human chorionic gonadotropin stimulated cholesterol biosynthesis significantly in the control animals, but failed to do so in the fluoride treated rams. Fluoride, also, reduced cholesterol biosynthesis in the treated groups compared with the control animals. Itw was postulated that fluoride might alter cholesterol biosynthesis by influencing carbohydrate and lipid metabolic pathways.